Encouraging majority support for immigrant access to health services: Multiple categorization and social identity complexity as antecedents of health equality. (July 2016) - Prati, Francesca; Crisp, Richard J.; Pratto, Felicia; Rubini, Monica
Health disparities between groups remain even after accounting for established causes such as structural and economic factors. The present research tested, for the first time, whether multiple social categorization processes can explain enhanced support for immigrant health (measured by respondents' behavioral intention to support immigrants' vaccination against A H1N1 disease by cutting regional public funds). Moreover, the mediating role of individualization and the moderating role of social identity complexity were tested. Findings showed that multiple versus single categorization of immigrants lead to support their right to health and confirmed the moderated mediation hypothesis. The potential in developing this sort of social cognitive intervention to address health disparities is discussed.